Common Client Issues in Counselling An Australian Perspective - Beel, Nathan; Chinchen, Christine; Machin, Tanya; du Plessis, Carol (Open textbook library., 2023)
Common Client Issues in Counselling: An Australian Perspective focuses on common mental health issues, such as grief and loss, anxiety, and depression, experienced by clients presenting for counselling. The focus throughout is on providing an Australian perspective, highlighting contemporary understandings, as well as suggesting practical and integrative responses to each common issue. All of the authors, reviewers, and editors work within Australian counselling settings, including private practice, not for profit organisations and academic contexts. By drawing on the authors’ extensive experience, and using a contextual rather than diagnostic approach, each chapter is brought to life with valuable insights and suggestions.